KONTRIBUSI PEMBELAJARAN PAK TERHADAP KEROHANIAN SISWA DI SMPN 122 JAKARTA UTARA - Iman Dian Djaya; Johni Hardori; Josia Pantja Paruntung (Bethel Press, 2020)
This study aims to test, determine, and analyze empirically about increasing the spiritual growth of students through PAK learning at SMPN 122 North Jakarta. The formulation of the problem in this study is whether there is an effect of PAK learning on the spiritual growth of students at SMPN 122 North Jakarta? The study population was 35 students of SMPN 122 North Jakarta. The research sample was 30 people, taken using the Stratified Random Sampling technique. The construction validity approach was carried out with orthogonal interactions twice and the calculation of the reliability coefficient was carried out using the Cronbach Alpha formula. The hypothesis proposed is that it should be assumed that there is a positive and significant relationship between the effect of PAK Learning on the Spiritual Growth of Students at SMPN 122 North Jakarta. From the analysis of the hypothesis test for variable x, it is concluded that PAK Learning is 65.4%, which means that the level of influence of PAK Learning is very strong. The results of the data analysis show that the effect of PAK Learning on Student Spiritual Growth is 65.4% with very strong variable interpretation at the significance level of 0, 05. This shows that the effect of PAK Learning on the Spiritual Growth of Students at SMPN 122 North Jakarta contributed 0.65.4% or 65.4% and the remaining 34.6% was influenced by other variables which in this study were not examined. The conclusion obtained by the researcher is that